Atmospheric Processing of Loess Particles in a Polluted Urban Area of Northwestern China. Issue 14 (22nd July 2019) - Chen, Yang; Liu, Huanwu; Huang, Ru‐Jin; Yang, Fumo; Tian, Mi; Yao, Xiaojiang; Shen, Zhenxing; Yan, Lulu; Cao, Junji
Abstract: Loess is an important dust component of airborne particles in Northwestern China. Knowledge of the chemical composition, mixing state, and processing of loess particles in urban plumes is still limited. Urban loess particles were characterized using a single‐particle aerosol mass spectrometer. To understand sources and processing of loess particles, source samples from the road, urban background, soil, construction, and biomass burning ash were collected in the urban areas and characterized. Loess particles were determined as a kind of calcium‐silicate‐rich ones, which were internally mixed with calcium, silicates, potassium, elemental carbon, organics, ammonium, sulfate, and nitrate. Road and soil were major sources of loess particles. Among the aged loess particles, the average peak areas of taken‐up nitrate and sulfate were comparable to that of (Fe+Ca+Al). Diurnal uptake profiles of chloride, sulfate, oxalate, and nitrate on loess particles were analyzed. The nocturnal elevation of chloride occurred significantly due to the uptake of HCl (g). Nighttime nitrate formation occurred prevalently under high relative humidity conditions via the heterogeneous hydrolysis of N2 O5 . The nighttime enrichment of oxalate, which is a marker for aqueous‐formatted secondary organic aerosol, was also found. Besides the nighttime chemistry, the daytime photochemical activities were also a drive for the elevations of sulfate, nitrate, and ammonium. Conclusively, the processing of loess particles in polluted urban plumes significantly altered their chemical composition and mixing state. Key Points: Road and soil dust were major sources of ambient loess particles in Xi'an Airborne loess particles were significantly processed in the urban plume Nighttime chemistry was important for the uptake of nitrate and chloride to loess particles